BRAF V600E and retinoic acid in radioiodine-refractory papillary thyroid cancer - Gröner, Jan; Gelen, Debora; Herpel, Esther; Kender, Zoltán; Haufe, Sabine; Haberkorn, Uwe; Sulaj, Alba; Zemva, Johanna; Kopf, Stefan; Nawroth, Peter Paul; Brune, Maik; Rudofsky, Gottfried (Hormone and metabolic research, 2019)
Radioiodine refractoriness in differentiated thyroid cancer remains an unsolved therapeutic problem. Response to retinoids might depend on specific genetic markers. In this retrospective analysis, associations between BRAF V600E and clinical outcomes after redifferentiation with retinoic acid (RA) and radioiodine therapy (RIT) were investigated. Thirteen patients with radioiodine-refractory (RAI-R) papillary thyroid cancer (PTC) were treated with 13-cis-RA followed by iodine-131 treatment at the Department of Endocrinology, Heidelberg University Hospital, Heidelberg, Germany. DNA sequencing was performed in formalin-fixed paraffin-embedded tissue. Clinical outcome parameters were tumor size, thyroglobulin, and radioiodine uptake in correlation to mutational status. Differences of each parameter were compared before and after RA/RIT. Initial response showed no difference in patients with BRAF V600E compared to patients with wild type. However, after a median follow-up of 2 and a half years, 2 out of 3 patients with BRAF V600E showed response compared to 5 out of 9 with wild type under consideration of all 3 parameters. In this small cohort, more RAI-R PTC patients with BRAF V600E receiving redifferentiation therapy showed response. Verification in a larger study population analyzing mutational status in patients with RAI-R PTC might be helpful to identify patients where redifferentiation therapy might lead to an improved outcome.
05. November 2018 (efirst)
Gesehen am 16.05.2019